Adaptive Denoising of Images using Single Layer Neural Network and Normalized Signed Regressor LMS Algorithm - Sarangi, Sunita; Rath, Nrusingha Prasad; Kumar Sahoo, Harish (2019 IEEE 5th International Conference for Convergence in Technology (I2CT), 2019)
Denoising of images is very important aspect during image enhancement process. In this paper, a novel image denoising model based on adaptive threshold estimation using functional link artificial neural network (FLANN) is proposed. The proposed FLANN structure is trained by Normalised Signed Regressor LMS Algorithm (NSRA). The denoising model uses a second-order difference operator and median filtering that work on only degraded pixels. The method is tested with different test images under various noise ratios that the performance of proposed technique provides a significant improvement over other existing methods.